Anxiety and Depression in Drug-Dependent Patients with Cluster C Personality Disorders - Roncero, Carlos; de Miguel, Adelia; Fumero, Ascensión; Abad, Alfonso C.; Martín, Rita; Bethencourt, Juan Manuel; Grau-López, Lara; Rodríguez-Cintas, Laia; Daigre, Constanza (Frontiers in Psychiatry, 2018)
Objective: Comorbidity between Personality Disorders (PD) and Substance Use Disorders (SUD) is one the most common. The patients with Cluster C disorders present maladjustment traits often characterized by high levels of anxiety. The main aim of this study was to find evidences about higher anxiety and depression prevalence on Cluster C than others Clusters, analyzing similarities and differences within, with other Cluster A&B PD patients and patients without PD. Method: A total of 822 substance dependent patients (ages18-78; Mean=38.35, SD=10.14) completed the Structured Clinical Interview for DSM-IV Axis I and Axis II disorders, Beck Depression Inventory and State-Trait Anxiety Inventory. Results: Results supported poly-consumption in Cluster C patients, being greater alcohol consumption as well as abuse of both stimulants and depressants. Anxiety and depression did not show just one pattern for all patients with SUD-Cluster C PD. There was a relation between anxiety and depression for all the groups except for the Dependent-PD. Conclusions: Interventions should focus on aspects like depression and anxiety more than on the substance consumed.